2015
DOI: 10.3390/biom5020808
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and the Homeodynamics of Iron Metabolism

Abstract: Iron and oxygen share a delicate partnership since both are indispensable for survival, but if the partnership becomes inadequate, this may rapidly terminate life. Virtually all cell components are directly or indirectly affected by cellular iron metabolism, which represents a complex, redox-based machinery that is controlled by, and essential to, metabolic requirements. Under conditions of increased oxidative stress-i.e., enhanced formation of reactive oxygen species (ROS)-however, this machinery may turn int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
126
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(143 citation statements)
references
References 389 publications
(449 reference statements)
4
126
0
1
Order By: Relevance
“…In addition, the local lysosomal degradation of IONPs has been empirically demonstrated4 and the transfer of 59 Fe from IONPs to the hemoglobin of rats6 and mice7 was established. On the other hand, ferritins are able to antagonize lysosomal iron overload and oxidative stress by being relocalized in lysosomes or synthesized de novo 294950. However neither the transfer of metal ions from nanoparticles to ferritin was formally demonstrated, nor the transfer within environments exhibiting acidic pH going below 5.5 has been reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the local lysosomal degradation of IONPs has been empirically demonstrated4 and the transfer of 59 Fe from IONPs to the hemoglobin of rats6 and mice7 was established. On the other hand, ferritins are able to antagonize lysosomal iron overload and oxidative stress by being relocalized in lysosomes or synthesized de novo 294950. However neither the transfer of metal ions from nanoparticles to ferritin was formally demonstrated, nor the transfer within environments exhibiting acidic pH going below 5.5 has been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Our focus was to get insight into the role of ferritin proteins in the intracellular recycling and remediation of metal oxide nanoparticles and to examine if Co 2+ and Fe ions released by NPs can be stored into endogenous ferritin proteins. Ferritin proteins are implicated in various metabolic processes28, owing to their ability to detoxify, carry, store and release iron in a controlled fashion29. It has been shown that ferritins also act as a multifunctional detoxicant for soluble metal ions other than iron30313233.…”
mentioning
confidence: 99%
“…The storage of free iron especially becomes cytoprotectant when increased levels of heme degradation from vascular disruption are present. Ferritin (FTH1) is a protein whose function is to oxidize and store free iron as a protectant against oxidative stress [103, 128, 135] and can be influenced by cellular oxygen and inflammatory secreted cytokine levels [136]. FTH1 significantly upregulated with DFX treatment at the 48-hr (Figure 2) as compared to the un-treated (control) group, suggesting DFX could have influenced intracellular storage of free iron rather than its complete sequester and removal.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 CLIC5A could perturb this process and thereby impact cellular iron concentrations and modulate lysosome sensitivity to hydrogen peroxide. Interestingly, double positive staining appears to be particularly present in distinct vesicle-like structures that are likely transferrin receptor-containing recycling endosomes, further suggesting that CLIC5A may interfere with normal iron homeostasis, thus reducing lysosome sensitivity to oxidative stress.…”
mentioning
confidence: 99%